Devised Drama as Social-Emotional Learning - Kathleen R. McGovern; Vahdat Yeganeh (Anglica. An International Journal of English Studies)
This qualitative case study explores social-emotional learning (SEL) in an extracurricular drama program in the US, where adult English for Speakers of Other Languages (ESOL) students collaboratively devised a play, which they performed publicly. The authors drew from CASEL’s (2020) SEL framework, which consists of five core competencies, to explore drama as an SEL process. The findings indicate that devised drama engaged learners in activities that cultivated awareness of the self and others, created space for students to explore their emotions in a supportive community, and centered learner voices, indicating drama’s potential as an innovative SEL pedagogy within and beyond traditional learning spaces.